Epidemiology of newly diagnosed hypertensives in a tertiary care hospital in a developing country - Udaya Ralapanawa; Samath D. Dharmaratne; KushaleePoornima Jayawickreme; Madhushanka Ekanayake (Clinical and Experimental Hypertension, 2017)
Background: Cardiovascular diseases are the main cause of death in most countries and the past two decades have shown a global increase. Hypertension (HTN) was found to be the leading risk factor in 2010 as qualified by Disability Adjusted Life Years. Epidemiological studies in this regard in Sri Lanka are scarce. Thus, describing epidemiological patterns of HTN in the Sri Lankan population will help policy makers in planning preventive healthcare programs and aid in preparing strategies to cope with the increasing demand for healthcare facilities. Methods: This is a cross-sectional descriptive study conducted at the Teaching Hospital Peradeniya, Sri Lanka, among newly diagnosed hypertensives according to the JNC 7 report, attending the hypertensive clinic through referral. Data were collected by an interviewer administered structured questionnaire, and epidemiological patterns were analyzed. Results: Among 244 newly diagnosed hypertensives, the mean age was 58.3 years (SD = 12.3) and the majority were females. 66.8% had stage 2 HTN (>160 mmHg) at the time of first presentation to a tertiary care center. There was no statistically significant difference of the stage of HTN based on sex, education level, occupation, marital status, consumption of alcohol, and smoking. Conclusion: Majority of the population had very high blood pressure at first diagnosis, indicating delay in the detection of HTN at an early stage. Therefore, measures to increase the probability of early detection of HTN will be useful in reducing morbidity and mortality associated with HTN.